OBESITY AND PHYSICAL ACTIVITY LEVEL IN POLICE OFFICERS (Fiep Bulletin - online, 2015)
The aim of the study was to evaluate the physical activity level (PAL) and body mass index (BMI) of the police officer. It was evaluated 262 employees. 216 (82.4%) were male and 46 (17.5%) females with mean age 37±7.1 years. For assessing the PAL international physical activity questionnaire (IPAQ-8) was used and the BMI was calculated by dividing body weight (kg) by height (m2). The results of the PAL to the police were: 1.9% (n=5) very active, 30.1% (n=79) active, 51.5 % (n=135) irregularly active and 16.4% (n=43) sedentary. The results for BMI showed overall mean BMI 27.6±3.7 kg/m2. In conclusion, the study showed a high percentage of police officer classified as insufficiently active and within range of overweight and obese. These results demonstrate the need for educational and physical activity programs to control of body weight and physical inactivity within the military police.
Keywords: Motor Activity; Sedentary Lifestyle; Body Mass Index; Military.